Women in Professional Sport in India: Struggles for Equality and Recognition (International Journal of Scientific Research in Science and Technology, 2026)
Women’s participation in professional sport in India has increased significantly over the past two decades, driven by international success, government initiatives, and growing public visibility. Despite these advances, women athletes in India continue to face deep-rooted challenges related to equality and recognition. Drawing on national reports, academic research, and policy documents, this study examines the structural, economic, and socio-cultural barriers that limit women’s full participation in professional sport. Evidence suggests that while Indian women athletes have achieved global success in sports such as cricket, badminton, boxing, wrestling, hockey, and athletics, disparities persist in pay, media coverage, sponsorship, leadership representation, and access to professional infrastructure (Gupta, 2013; Naik&Bavadekar, 2024). Government schemes such as Khelo India, TOPS (Target Olympic Podium Scheme), and BetiBachaoBetiPadhao–linked sports initiatives have contributed to increased participation and financial assistance for women athletes. However, research indicates that policy support has not fully translated into professional equality, particularly in league-based sports where commercialization remains gender-biased (Chauhan, 2023). Media recognition continues to be uneven, with women’s sport receiving substantially less coverage than men’s cricket-centric sporting culture. This study adopts a quantitative research approach to analyze the experiences of women professional athletes across multiple sports in India. By integrating athlete perceptions with institutional data and national reports, the research seeks to highlight persistent inequalities and identify pathways for achieving equitable recognition and sustainable professional opportunities for women in Indian sport.